PARADIGMS OF MODERN LINGUISTICS IN THE GLOBALIZED WORLD - Abduraxmonova Gulsevar Maxsitali Qizi; Bazarbaeva Sarbinaz Tazabay Qizi; Khazratkulova Ezoza Ismat qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Modern linguistics is rapidly changing as a result of globalization, technological improvements, and increased interaction across languages and cultures. This study examines the major paradigms in contemporary language studies, with a focus on structuralism, functionalism, cognitive linguistics, sociolinguistics, and computational linguistics. Furthermore, the effects of globalization on language evolution, multilingualism, and linguistic identity are examined. The essay discusses how modern linguistic paradigms respond to the demands of a worldwide world and contribute to a better understanding of language dynamics.